COGNITIVE RESTRUCTURING: ALTERNATIVE COUNSELING TECHNIQUES TO REDUCTION ACADEMIC PROCRASTINATION - Sofiana, Annisa (Universitas Muhammadiyah Metro, 2016)
Procrastination is often experienced by almost everyone, including students who often delay to resolve any responsibility in the academic process that would decrease the individual academic achievement. cognitive restructuring is one of the cognitive techniques used in counseling in addition to cognitive behavioral techniques (behavioral) and didaktif techniques. This technique has several procedures by focusing on identifying an effort and changing dysfunctional thoughts or negative self-statements into a new belief that is more rational and adaptive, which will affect more rational behavior anyway. Cognitive restructuring techniques assessed to be an alternative counseling techniques in reducing academic procrastination.